Measuring party positions and issue salience with mass media and manifesto data: Comparing PolDem with Manifesto Project data - Theresa Gessler; Swen Hutter (Party Politics, 2026)
To what extent do measures of the issue positions and salience of political parties differ when they are extracted from mass media debates and election manifestos? Answering this question, the paper serves a dual purpose within this special issue of Party Politics : (i) introducing the PolDem election dataset used throughout the issue, and (ii) analyzing its convergence with the widely used Manifesto Project data. The newly released PolDem dataset, based on a relational content analysis of newspaper articles published during national election campaigns, covers 15 European countries and 111 campaigns. Focusing on four broad issue domains (economic, cultural, European integration, and political issues) across countries from Northwestern, Southern, and Central-Eastern Europe, the results demonstrate strong convergence in issue positions, except for in political issues related to democracy and corruption. However, the datasets differ significantly in issue salience, especially for less salient, noneconomic issues, niche parties and in less polarized contexts.
Keywords: 320; party competition; cross-validation; mass media; manifestos